Horizon 2020: The Grand Challenges Challenges and Opportunities - Žic Fuchs, Milena (2012)
Presentation focused on the role of SSH research in Grand Challenges as well as the so-called Sixth Grand Challenge, dedicated specifically to the Humanities and Social Sciences. The importance of Infrastructures in SSH as well as the global dimension of research were stressed.
Projekt MZOS
ENG